158 The Association Between Sleep Spindles and Cognitive Function in Middle-Aged and Older Men: A Population-Based Cohort Study. (3rd May 2021) - Parker, Jesse; Appleton, Sarah; Melaku, Yohannes; D'Rozario, Angela; Wittert, Gary; Catcheside, Peter; Adams, Robert; Vakulin, Andrew; Martin, Sean
Abstract: Introduction: Sleep spindles are thought to play an important role in learning and memory. The association between sleep spindles and cognitive function and the potential confounding influence of obstructive sleep apnea (OSA) is uncertain. We examined the cross-sectional association between sleep spindles and cognitive function controlled for OSA in a sample of community dwelling middle-aged and older men. Methods: Participants of the Florey Adelaide Male Ageing Study (n=477) underwent home-based polysomnography. These participants also completed the inspection time (IT) task, trail-making test part A (TMT-A) and part B (TMT-B), and Fuld object memory evaluation (FOME) test. Spindle metrics derived from sleep electroencephalography (n=356) included occurrence (total number) and fast (13-16 Hz) and slow (11-13 Hz) spindle density (number/minute) during N2 and N3 sleep. Linear regression models were adjusted for age, OSA, education, obesity, cardiovascular disease, diabetes, smoking, and alcohol risk. Results: In covariate unadjusted analyses, higher spindle occurrence during N2 sleep was associated with better IT, TMT-A, TMT-B, and FOME performance (all p<0.05). Spindle density (fast and slow) during N2 and N3 sleep (slow spindles only) was associated with better inspection time, TMT-A, and TMT-B performance (all p<0.05). Fast spindle density during N2 sleep was also associated with better FOME performance (B=1.03, 95% CI [0.47, 1.59], p<0.05). In covariate adjusted analyses, higher spindle occurrence during N2 sleep was independently associated with better IT (B=-0.002, 95% CI [-0.004, 0.000], p=0.046), while fast spindle density during N3 sleep was independently associated with worse TMT-B performance (B=0.12, 95% CI [0.03, 0.21], p=0.011). Conclusion: Specific sleep spindle metrics during N2 and N3 sleep were independently associated with better visual processing speed and worse executive attention, suggesting a differential association between cognitive function and spindles during N2 and N3 sleep. The utility of sleep spindles for predicting cognitive impairment needs investigation in prospective studies. Support (if any): National Health and Medical Research Foundation, Adelaide Institute for Sleep Health, Hospital Research Foundation, and ResMed Foundation.